Induced cumulus expansion of poor quality buffalo cumulus oocyte complexes by Interleukin‐1beta improves their developmental ability. Issue 7 (12th March 2018) - Chaubey, Gaurav Kumar; Kumar, Sandeep; Kumar, Manish; Sarwalia, Parul; Kumaresan, Arumugam; De, Sachinandan; Kumar, Rakesh; Datta, Tirtha Kumar
Abstract: The present study was conceived with the aim of modulating the cumulus expansion characteristics of poor quality (BCB−) buffalo oocyte complexes (COCs) in order to improve their fertilization outcomes. BCB− COCs were subjected to in vitro maturation (IVM) in presence of Interleukin‐1 beta (IL‐1β) along with BCB‐ (control) and good quality (BCB+) COCs. Results were assessed morphologically, by scanning electron microscopy (SEM) and by expression analysis of cumulus expansion related genes. Also, numbers of zona pellucida bound spermatozoa were counted and development rates of oocytes were monitored under different groups. Expression of versican isoforms and ADAMTS‐1 was observed to be significantly different between cumulus cells of BCB+ and BCB− COCs. Upon IL‐1β supplementation, ADAMTS‐1 expression increased in BCB− COCs along with corresponding cumulus expansion rates. SEM analysis also revealed improved cumulus expansion in IL‐1β supplemented BCB‐ COCs. HAS2 and TNFAIP‐6 were significantly up‐regulated after IL‐1β supplementation while PTGS2 expression remained unaffected. Significantly more numbers of sperms crossed the cumulus barrier, especially in 100 ng/mL IL‐1β supplemented COCs. Besides, cleavage and blastocyst development rates were also improved upon IL‐1β addition. We concluded that IL‐1β supplementation in IVM medium can improve cumulus expansion and development ability of poor quality buffalo oocytes. Abstract : Schematic picture showing hypothesis under study, results obtained and inferences drawn. IO (Immature oocyte). MO BCB+ (Mature oocyte BCB+), MO BCB− (Mature oocyte BCB−).